1988
DOI: 10.1128/jvi.62.11.4288-4295.1988
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction between coronavirus leader RNA and nucleocapsid protein

Abstract: Northwestern blot analysis in the presence of competitor RNA was used to examine the interaction between the mouse hepatitis virus (MHV) nucleocapsid protein (N) and virus-specific RNAs. Our accompanying article demonstrates that anti-N monoclonal antibodies immunoprecipitated all seven MHV-specific RNAs as well as the small leader-containing RNAs from infected cells. In this article we report that a Northwestern blotting protocol using radiolabeled viral RNAs in the presence of host cell competitor RNA can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
163
2
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 36 publications
4
163
2
1
Order By: Relevance
“…Furthermore, using an in vitro system, it was demonstrated that antibodies to the N protein, but not those against the S and M proteins, inhibited viral RNA synthesis by 90% (Compton et al, 1987). Interactions that have been observed between the N protein and leader/TRS sequences Nelson et al, 2000;Stohlman et al, 1988) and between N protein and the 3 0 UTR (Zhou et al, 1996) suggest a role for the N protein in the discontinuous transcription process. Furthermore, the N protein was also shown to interact with cellular proteins that play a role in coronavirus RNA replication and transcription (Choi et al, 2002;Shi et al, 2000).…”
Section: N Proteinmentioning
confidence: 96%
“…Furthermore, using an in vitro system, it was demonstrated that antibodies to the N protein, but not those against the S and M proteins, inhibited viral RNA synthesis by 90% (Compton et al, 1987). Interactions that have been observed between the N protein and leader/TRS sequences Nelson et al, 2000;Stohlman et al, 1988) and between N protein and the 3 0 UTR (Zhou et al, 1996) suggest a role for the N protein in the discontinuous transcription process. Furthermore, the N protein was also shown to interact with cellular proteins that play a role in coronavirus RNA replication and transcription (Choi et al, 2002;Shi et al, 2000).…”
Section: N Proteinmentioning
confidence: 96%
“…These features suggest that the N protein may be less stable than other structural proteins of SARS-CoV (Wang et al, 2004). Based on the available information from other coronaviruses, the N protein has been implicated in a variety of functions, including genomic RNA replication (Compton et al, 1987), subgenomic RNA transcription (Stohlman et al, 1988) and translation (Ulmanen et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…N protein binds to the RNA genome, forming a helical nucleocapsid (Escors et al, 2001;Sturman et al, 1980). N protein has a structural role in coronavirus assembly (Risco et al, 1996) and is a growing evidence for a role in RNA synthesis (Almazan et al, 2004;Baric et al, 1988;Stohlman et al, 1988). Some reports have been Veterinary Microbiology 172 (2014) Transmissible gastroenteritis coronavirus (TGEV) is an enteropathogenic coronavirus that causes diarrhea in pigs, which is correlated with high morbidity and mortality in suckling piglets.…”
Section: Introductionmentioning
confidence: 99%